DISCRETION POWER: The Constitutional court of Bosnia and Herzegovina as a "political court"? - Savanović, Aleksandar (Politeia, 2017)
This paper analyzes the political crisis produced in BiH society by decisions of the Constitutional Court of Bosnia and Herzegovina for cases U-3/13, U-18/16 and U-22/16. These cases are important case studies for the classical problem of political philosophy and contemporary jurisprudence – namely: a power direction problem of the highest judicial institution (Supreme or/and Constitutional courts). Must the highest judicial institution be “political” by definition? Or is the “political” influence of Supreme/Constitutional courts a result of their own intention to expand their power and influence? The role, practice and legacy of the highest judicial institution in an extremely divided society, such as BiH, is a kind of real-time experiment for this problem.